Proposed Corporate Strategy of PT. Pikiran Rakyat Bandung - Noezar, Firra Astria; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
PT. Pikiran Rakyat Bandung (PT. PRB) is a region-level conventional newspaper company positioned on the 8th biggest market share of newspaper in Indonesia with 5.89% market share in year 2005. Today, the using of mobile phone and internet has risen to 62% and 42%. Indonesians are expected to be very responsive to the development of gadget and internet. This era is feared by PT. PRB can bring down the company. One of the symptoms is the decreasing of the revenue from year 2010-2012 by 1.4% in year 2011 and 3.12% in year 2012. The company has intention to do early precautionary strategy before the decreasing goes too far. Methodology in this final project is by evaluating the external and internal environment in order to get the SWOT. From the SWOT, corporate strategy can be created using TOWS matrix and Grand Selection Matrix. The building of the Grand Selection Matrix is supported by IFAS and EFAS table. After generating the corporate strategy, evaluation is done using cost and benefit analysis. Using the method above, it is found that the score of IFAS and EFAS are 2.21 and 2.00 respectively. Therefore, it is located in the third quadrant which is retrenchment strategy. The cost and benefit analysis resulting weighted score of 1.63 for conglomerate diversification which is the best solution for the company. To implement the strategy there are several actions should be done in 5 years of time horizon.Â Keywords: Internal Analysis, External Analysis, Strategy Formulation, Corporate Strategy, Information Industry, Newspaper Business